Comparison of the lower limit of normal to the fixed ratio method for the diagnosis of airflow obstruction at high altitudes: a large cross-sectional survey of subjects living between 3000–4700 m above sea level - Huang, Yilin; Xing, Zhenzhen; Janssens, Jean-Paul; Chai, Di; Liu, Weiming; Wang, Yuxia; Mayordome, William Yali-Mona; Tong, Yaqi; Guo, Yanfei (European Journal of Medical Research, 2023)
Background There is no general agreement on the preferential use of a fixed ratio (FR) of forced expiratory volume in 1 s (FEV 1 )/forced vital capacity (FVC) < 0.7 vs. the lower limit of normal (LLN) of FEV 1 /FVC to define airflow obstruction. Determining the impact of these different cut-off levels in people living at high altitudes has not been studied. We assessed the prevalence of airflow obstruction and its clinical characteristics in residents living at high altitude using a fixed ratio and the LLN of FEV 1 /FVC according to Global Lung Initiative 2012 (GLI) reference values. Methods Using a multistage stratified sampling method, 3702 participants (aged ≥ 15 years) living at an altitude of 3000–4700 m in Tibet were included. Results 11.4% and 7.7% of participants had airflow obstruction according to GLI-LLN and a fixed FEV 1 /FVC cut-off value, respectively. The participants in the FR−/LLN+ group were younger, predominantly female, more frequently exposed to household air pollution, and had a higher proportion of chronic obstructive pulmonary disease assessment test scores ≥ 10 than those in the FR−/LLN− group. They also had a significantly lower FEV 1 and a higher frequency of small airway dysfunction. Compared with the participants of the FR+/LLN+ group, those in the FR−/LLN+ group showed no significant difference in the risk factors for airflow obstruction and respiratory symptoms, but had a lower prevalence of small airway dysfunction. Conclusions Defining airflow obstruction according to LLN, instead of using an FR, identified younger individuals with more frequent clinical symptoms of airflow obstruction and small airway dysfunction.